Enhancing biomass utilization by combined pulp and fuel production - Granacher, Julia; Nguyen, Tuong-Van; Castro-Amoedo, Rafael; McDonald, Erina Clare; Maréchal, François (Frontiers in Energy Research, 2022)
A shift from fossil fuels to renewable energy sources is essential to reduce global greenhouse gas emissions and climate change effects. Biofuels represent a promising low-carbon alternative for sectors that are hard to electrify, such as freight transport or aviation. This work investigates possible pathways for increasing the value of biomass at a Kraft pulp mill, focusing on black liquor and bark streams. Mathematical programming is coupled with superstructure optimization and systematic solution exploration to identify meaningful process configurations. The analysis of solutions under market variations allows for the identification of robust and competitive configurations for the co-production of pulp and fossil fuel alternatives. The results show that the integration of biorefineries in pulp mills results in better resource use and higher energy efficiency - diversifying the product portfolio and providing bio-based fuel products to the market while being economically viable. By incorporating fuel production in the conventional Kraft process, the carbon conversion efficiency of the mill can be increased from 48% to up to 67%. Extending the analysis, up to 2% of the European road freight transportation fuel could be provided with combined pulp and fuel production, and 5% of the worldwide fuel demand for passenger aviation.